2011
DOI: 10.1017/s0033291711001152
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring as a familial vulnerability marker for psychosis: an analysis of patients, unaffected siblings and healthy controls

Abstract: BackgroundAlterations in self-monitoring have been reported in patients with psychotic disorders, but it remains unclear to what degree they represent true indicators of familial vulnerability for psychosis.MethodAn error-correction action-monitoring task was used to examine self-monitoring in 42 patients with schizophrenia, 32 of their unaffected siblings and 41 healthy controls.ResultsSignificant between-group differences in self-monitoring accuracy were found (χ2=29.3, p<0.0001), patients performing wors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 87 publications
(123 reference statements)
1
10
0
Order By: Relevance
“…Various authors have demonstrated that thresholds for the recognition of discrepancies between motor movements and their consequences varies from individual-to-individual and performance corrections are driven by unconscious error correction systems that rely on the integration of visual and motor information (Fourneret and Jeannerod, 1998; Slachevsky et al, 2001; Slachevsky et al, 2003; Knoblich and Kircher, 2004; Spape and Serrien, 2010). Deficits in these functions have been reported in people diagnosed with schizophrenia (Knoblich et al, 2004) and their first degree biological relatives (Hommes et al, 2011), and poor visuomotor action monitoring has been found to correlate with scores on measures of positive schizotypy (Hommes et al, 2011). These results suggest that people diagnosed with or at increased risk for schizophrenia (i.e., schizotypes; Meehl, 1990; Lenzenweger, 2010) take longer to notice and make corrections for discrepancies between intended and actual movements.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Various authors have demonstrated that thresholds for the recognition of discrepancies between motor movements and their consequences varies from individual-to-individual and performance corrections are driven by unconscious error correction systems that rely on the integration of visual and motor information (Fourneret and Jeannerod, 1998; Slachevsky et al, 2001; Slachevsky et al, 2003; Knoblich and Kircher, 2004; Spape and Serrien, 2010). Deficits in these functions have been reported in people diagnosed with schizophrenia (Knoblich et al, 2004) and their first degree biological relatives (Hommes et al, 2011), and poor visuomotor action monitoring has been found to correlate with scores on measures of positive schizotypy (Hommes et al, 2011). These results suggest that people diagnosed with or at increased risk for schizophrenia (i.e., schizotypes; Meehl, 1990; Lenzenweger, 2010) take longer to notice and make corrections for discrepancies between intended and actual movements.…”
Section: 0 Discussionmentioning
confidence: 99%
“…These studies include the following questionnaire studies: the schizotypal experience scales (linked with ESS; Launay and Slade, 1981 ; Claridge and Broks, 1984 ; Bentall et al, 1989 ; Raine, 1991 ; Mason et al, 1995 ; Waters et al, 2003 ; Cyhlarova and Claridge, 2005 ; Sugimori et al, 2009 ), depersonalization scales (linked with ownership; Putnam, 1997 ; Sierra and Berrios, 2000 ), and agency or minimal self scales ( Parnas et al, 2005b ; Asai et al, 2009b ). We also considered many other empirical, theoretical, and phenomenological studies to prepare for potential new items (e.g., Cahill, 1996 ; Iriki et al, 1996 ; Daprati et al, 1997 ; Botvinick and Cohen, 1998 ; Blakemore et al, 2000 ; Frith et al, 2000a ; Peled et al, 2000 ; Fourneret et al, 2001 ; Franck et al, 2001 ; Platek and Gallup, 2002 ; Wegner, 2003 ; Blanke, 2004 ; Knoblich and Kircher, 2004 ; Maravita and Iriki, 2004 ; Sato and Yasuda, 2005 ; Asai and Tanno, 2007 , 2008 , 2013 ; Jones and Fernyhough, 2007 ; Asai et al, 2008 , 2009a , 2011 ; David et al, 2008 ; Longo et al, 2008 ; Johns et al, 2010 ; Newport et al, 2010 ; Hauser et al, 2011 ; Hommes et al, 2011 ; Sugimori et al, 2011a , b , 2012 ; Sugimori and Asai, 2015 ). Ownership was assumed to include items like “Sometimes it feels like my body is jerky like a robot.” Agency might include “I sometimes bump into things or people when I am out walking.” Continuity might include “I cannot remember what I did during that period because my memory was fuzzy.” Uniformity might include “Sometimes I feel that I no longer know my own personality.” A tense and an expression for items were unified so that a higher score on a five-point Likert scale means a more anomalous ESS.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment of these patients with clondine or guanfacine (α 2 adrenergic agonist) causes reduced functioning of NA receptors, improved cognitive functioning as measured by learning, delayed recall, and the Trail B task (Fields et al, 1988;Friedman et al, 1999). Deficits in self-monitoring have been hypothesized to be the cause of the auditory illusions in some schizophrenic patents; what exactly the effects are of abnormally high NA levels remains to be investigated (e.g., Wilkinson, 2014;Hommes et al, 2012).…”
Section: Neurological Disordersmentioning
confidence: 99%